2011
DOI: 10.1016/s2255-4971(15)30407-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Low-Level Laser Therapy in Patients With Knee Osteoarthritis: A Randomized Placebo-Controlled, Double-Blind Clinical Trial

Abstract: Objective: This study was designed to evaluate the short-term efficacy of low-level laser therapy (LLLT) for improving pain and function in patients with knee osteoarthritis. Methods: Forty-seven patients with knee osteoarthritis (79 knees), of both genders, participated in this randomized controlled double-blind clinical trial. They were randomly allocated to two groups: laser group with 25 patients (41 knees) and placebo group with 22 patients (38 knees). LLLT was performed three times a week, totaling nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
3
21
2
3
Order By: Relevance
“…These results are consistent with Fukuda et al [41] who investigated the effect of LLLT using GaAs laser. They revealed that treatment with LLLT alleviated pain and improved functional ability over the short term, among patients with knee osteoarthritis.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with Fukuda et al [41] who investigated the effect of LLLT using GaAs laser. They revealed that treatment with LLLT alleviated pain and improved functional ability over the short term, among patients with knee osteoarthritis.…”
Section: Discussionsupporting
confidence: 92%
“…However, in Fudka et al study, a laser with a wavelength of 904 nm was used in patients with knee osteoarthritis for three days a week PHYSICAL TREA MENTS and 9 sessions. In this study every point was emitted with 3 Jules power and finally the study result showed effectiveness of laser, compared with the placebo in reducing pain and improving function [22]. Our study was similar to Bulow et al study who emitted laser with wavelength of 830 nm and a total dose of 22.5 Jules on 9 points around the knee.…”
Section: Discussionsupporting
confidence: 84%
“…Evidence strongly suggests that laser can reduce acute pain with modulation of inflammatory markers such as PGE2, mRNA Cox 2, IL-1β, TNFα [21]. Moreover, laser can repair joint cartilage, proliferate cartilage cells, and synthesize and secret the extracellular matrix [22]. Ohshiro study showed that the laser had positive effects on blood flow and temperature, and thereby on reducing pain [23].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies 14,16,17,19,24,26 including 689 patients (354 LLLT and 335 placebo) assessed the pain in activity outcomes of the patients. The overall inverse variance pooled SMD calculated for pain in activity was -0.31 (95% CI; -0.55, -0.07) in favor of the LLLT (P = 0.01, Figure 4).…”
Section: -2-pain In Activitymentioning
confidence: 99%
“…29 Four studies 13,16,17,25 including 304 patients (137 LLLT and 167 placebo) assessed the range of motion outcomes of the patients. The overall inverse variance pooled SMD calculated for range of motion was 0.63 (95% CI; -0.13, 1.4).…”
Section: -Range Of Motionmentioning
confidence: 99%